0279 Thermoneutral temperature exposure increases slow-wave sleep in the 3xTg-AD mouse model of Alzheimer's Disease. (25th May 2022) - Wang, Jun; Huffman, Dillon; Ajwad, Asma'a; Bachstetter, Adam; Murphy, Michael; O'Hara, Bruce; Duncan, Marilyn; Sunderam, Sridhar
Abstract: Introduction: There is growing evidence that disordered sleep, which is known to be associated with Alzheimer's disease (AD), may accelerate neuropathology, thus promoting a vicious cycle. Strategies for improving sleep quality may slow disease progression. Here we investigate the feasibility of sleep enhancement through ambient temperature regulation and examine the effect on amyloid pathology. Methods: Female 3xTg-AD mice (~12 m.o.) were instrumented for EEG/EMG monitoring. After a week-long baseline, one half of the mice (n=8, EXPT) were exposed to stepwise diurnal increases in ambient temperature (Ta) to reach 30oC (thermoneutral for mice) during the light phase while the rest (n=8, CTRL) remained at room temperature (22oC). Vigilance state – i.e., Wake, REM, NREM, and slow wave sleep (SWS) within NREM – was scored in 4-second epochs and sleep metrics were computed. Results: SWS percentage became significantly greater (p<0.05) in the light phase for EXPT mice over the course of treatment. These effects suggest better sleep consolidation and greater sleep depth with thermoneutral warming. After four weeks of treatment, the animals were euthanized, and the brains removed to assay amyloid pathology by ELISA. We found that thermoneutral warming caused a significant reduction in both Aβ40 and Aβ42 in the hippocampus, but not in the cortex. Conclusion: These data imply that thermoneutral warming might have some regional specificity in its effects. The effects appear to be specific to some brain areas more than others, with implications for the cognitive and neuropathologic changes found in AD. Furthermore, since SWS and REM support memory, future studies should investigate the effects of thermoneutral enhancement of SWS and REM on cognition. Support (If Any): R01AG068215; seed funds UKY Department of Neuroscience